Simulation On The Performance of a Stirling Cooler For Use in Solar Powered Refrigerator - Daffallah Ahmed, Khalid Osman (2004)
Solar electricity produced bj. photovoltaic (PV) solar cells is one of the promising sources of power for solar refrigerator. Presently, solar PV is used to power conventional vapor compression or Rankine refrigerators. In this work, three photovoltaic freezers with different capacities and volumes of 100, 230 and 330 liters have been designed and tested. The freezers used the conventional vapor compression Rankine cycle. For the 100-liter freezer a minimum cabinet temperature of -20.1°C was obtained. The maximum and minimum cooling capacity were semi-empirically computed to be 304W and 85.8W and the corresponding power consumptions were 139W and 70.1 W respectively. Coefficient of performance was calculated to be 2.19 and 1.22 respectively at the maximum and minimum temperatures. For the 230-liter freezer, a temperature of -1 5.2"C was achieved. The cooling capacity. power consumption, coefficients of performance \+ere obtained semi-empiricall!~. Similar experimental analysis was done on the 330-liter freezsr to achieve a temperature of -5°C. All these freezers were tested for condenser teniperati~reo f 54°C and ambient temperature of 38°C.Limitations of the vapor compression refrigerator were highlighted; these include insufficient power from the 75W solar panel to run the refrigerator's compressor and therefore a backup battery is always required. But, battery is expensive and has a limited charge /discharge cycles. To allow for the use of photovoltaic module to power bigger size refrigerator, a new age of refrigeration technology such as a free piston Stirling cooler is used to replace the vapor compression refrigerator. The free piston Stirling cooler uses small amount of power effectively besides elimination of battery since free piston Stirling cooler can use phase change material to store cooling when there is insufficient power (low solar insolation and night time operation). The general principle in which a Stirling machine self-limits its operation was presented. The proposed design of the Stirling cooler was described and 'the performances of the cooler were simulated using the MATLAB computer software. Three types of analyses were carried out i.e. ideal adiabatic, Schmidt and non-ideal adiabatic. Results from the ideal adiabatic analysis showed that the total power output was 101.2W. Coefficient of performance of 3.6 was obtained, which was found to be about 21.5% of the Carnot COP. The COP was calculated for cold space temperature of -1 0°C and warm space temperature of 27°C. The heat absorbed by the acceptor was found to be 44.28W while the heat released by the rejector was computed to be 56.51 W.For isothermal conditions of the working space and heat exchangers, Schmidt analysis was carried out for cold space temperature of -lO°C and warm space temperature of 23OC. From the MATLAQ results, work done on the expansion and by the compression spaces were found to be 8.813~10" and -9.283~10-'J respectively. Total work done was calculated to be 1.1451~0 -'J. The effects of the non-ideal heat exchangers and the difference in the working gas and wall temperatures were determined through a non-ideal adiabatic analysis. The gas temperature was obtained through iteration until convergence was achieved. Coefficient of performance of 3.8 was obtained for ideal regenerator and then reduced to 2.4 for a non-ideal regenerator when pumping loss was taken into account for the same temperatures of the working spaces. Performance of operation, in terms of power consumption and cooling capacity, of the vapor compression refrigerator and Stirling type refrigerator was carried out. The comparison was based on the experimental data obtained for the vapor compression refrigerator and output data derived from MATLAB analysis for the Stirling refrigerator. The power consumption of the Stirling refrigerator was calculated to be 20W while that of the vapor compression was computed to be 139W.